γ-oryzanol content screening in local brown rice samples from Chiang Mai, Thailand and comparison between uncooked and cooked brown rice - Surat Hongsibsong (2018)
© 2016 Surat Hongsibsong et al. All rights reserved. Brown rice is the rich source of γ-oryzanol, which is important bioactive compounds and nutraceuticals with numerous potential health functions. So, promotion of brown rice consumption among consumer would be having data on γ-oryzanol in rice difference varieties as an alternative for selecting. The aim of present study was to determine γ-oryzanol in brown rice from 4 districts of Chiang Mai province, Northern Thailand and effected of cooking processes by streaming. The brown rice samples were from Mae-Cham, Om-Koi, Kanlayaniwattana and Chiang-Dao district and analyzed by modified HPLC with U/V detection. The γ-oryzanol content in raw brown rice samples were from 34.98-71.13 mg g-lraw brown rice and cooked brown rice were from 12.7-80.79 mg g-lraw brown rice. The most of γ -oryzanol content after cooking by streaming was decreased except some varieties i.e., Jao Luang, Nuk Roo, Kao Pum and Bue Ta Kree. The rice varieties that had increasing content of γ-oryzanol should be promoted to consume as good food and nutraceuticals health product.